Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{13+x}{20}=\frac{3}{4}\)
\(\Rightarrow\frac{13+x}{20}=\frac{15}{20}\)
\(\Rightarrow13+x=15\)
\(\Rightarrow\) \(x=15-13\)
\(\Rightarrow\)\(x=2\)
b)\(\frac{23-x}{25}=\frac{4}{5}\)
\(\Rightarrow\frac{23-x}{25}=\frac{20}{25}\)
\(\Rightarrow23-x=20\)
\(\Rightarrow\) \(x=23-20\)
\(\Rightarrow\) \(x=3\)
a, 13+x/20= 3/4
Suy ra: ( 13+x). 4= 20.3
Suy ra: (13+x).4=60
Suy ra: 13+x=60:4
Suy ra: 13+x=15
Suy ra: x=15-13
Suy ra: x=2
Vậy x=2
![](https://rs.olm.vn/images/avt/0.png?1311)
(x-1/2)*5/3=7/4-1/2
(x-1/2)*5/3=5/4
x-1/2=3/4
x = 5/4
(x+4/3)*7/4=5-7/6
(x+4/3)*7/4=23/6
x+4/3 = 46/21
x = 6/7
6/8=15/x
6*x=15*8
6*x=120
x = 20
\(\frac{6}{8}=\frac{15}{x}\)
\(\Rightarrow x=\left(15\cdot8\right):6\)
\(\Rightarrow x=20\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{3}{5}+\frac{6}{11}+\frac{7}{13}+\frac{5}{11}+\frac{2}{5}+\frac{19}{13}=\left(\frac{3}{5}+\frac{2}{5}\right)+\left(\frac{6}{11}+\frac{5}{11}\right)+\left(\frac{7}{13}+\frac{19}{13}\right)=1+1+2=4\)
b) \(\frac{6}{5}\times\frac{3}{8}+\frac{5}{8}\times\frac{6}{5}-\frac{4}{5}=\frac{6}{5}\times\left(\frac{3}{8}+\frac{5}{8}\right)-\frac{4}{5}=\frac{6}{5}-\frac{4}{5}=\frac{2}{5}\)
c) \(\frac{4\times5\times6\times7\times8}{8\times10\times12\times14\times16}=\frac{1}{2\times2\times2\times2\times2}=\frac{1}{32}\)
a, \(\frac{3}{5}+\frac{6}{11}+\frac{7}{13}+\frac{6}{11}+\frac{2}{5}+\frac{19}{13}\)
\(=\left(\frac{3}{5}+\frac{2}{5}\right)+\left(\frac{7}{13}+\frac{19}{13}\right)+\left(\frac{6}{11}+\frac{6}{11}\right)\)
\(=1+2+\frac{12}{11}\)
\(=3+\frac{12}{11}\)
\(=\frac{45}{11}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a. \(\frac{-3}{2}-2x+\frac{3}{4}=-22\)2
=> \(-2x=-22+\frac{3}{2}-\frac{3}{4}\)
=> \(-2x=\frac{-85}{4}\)
=> \(x=\frac{-85}{4}:\left(-2\right)\)
=> \(x=\frac{85}{8}\)
b. \(\left(\frac{-2}{3}x-\frac{3}{5}\right).\left(\frac{3}{-2}-\frac{10}{3}\right)=\frac{2}{5}\)
=> \(\left(\frac{-2}{3}x-\frac{3}{5}\right).\frac{-29}{6}=\frac{2}{5}\)
=> \(\frac{-2}{3}x-\frac{3}{5}=\frac{2}{5}:\left(\frac{-29}{6}\right)\)
=> \(\frac{-2}{3}x-\frac{3}{5}=\frac{-12}{145}\)
=> \(\frac{-2}{3}x=\frac{-12}{145}+\frac{3}{5}\)
=> \(\frac{-2}{3}x=\frac{15}{29}\)
=> x = \(\frac{15}{29}:\frac{-2}{3}\)
=> x = \(\frac{-45}{58}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(\frac{8}{13}+\frac{4}{9}+\frac{1}{3}+\frac{5}{13}+3\)
\(=\left(\frac{8}{13}+\frac{5}{13}\right)+\left(\frac{4}{9}+\frac{1}{3}\right)+3\)
\(=1+\left(\frac{4}{9}+\frac{3}{9}\right)+3\)
\(=1+\frac{7}{9}+3\)
\(=1+3+\frac{7}{9}\)
\(=4\frac{7}{9}\)
\(=\frac{43}{9}\)
b)\(\frac{8}{5}\cdot\frac{4}{7}+\frac{4}{7}\cdot\frac{2}{5}-1\)
\(=\frac{4}{7}\cdot\left(\frac{8}{5}+\frac{2}{5}\right)-1\)
\(=\frac{4}{7}\cdot2-1\)
\(=\frac{8}{7}-1\)
\(=\frac{1}{7}\)
a) \(\frac{8}{13}+\frac{4}{9}+\frac{1}{3}+\frac{5}{13}+3\)
\(=\left(\frac{8}{13}+\frac{5}{13}\right)+\left(\frac{4}{9}+\frac{3}{9}\right)+3\)
\(=1+\frac{7}{9}+3=4\frac{7}{9}\)
b)\(\frac{8}{5}.\frac{4}{7}+\frac{4}{7}.\frac{2}{5}-1\)
\(=\frac{4}{7}.\left(\frac{8}{5}+\frac{2}{5}\right)-1\)
\(=\frac{4}{7}.2-1\)
\(=\frac{8}{7}-\frac{7}{7}=\frac{1}{7}\)
\(\frac{\left(13+X\right):3}{20:4}=\frac{\left(13+X\right):3}{5}\)
Khi rút gọn phân số thì X sẽ bằng: (5x3) -3 = 2
\(\frac{23-x}{25}=\frac{4}{5}\)
25:5= 5
x= 23 - ( 4 x 5 )
x=2